Light protection of cycle lanes: Best practices - Brian Deegan (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This report reviews the effectiveness of light separation as an alternative to more permanent infrastructure to protect cycle lanes. With more cyclists on the roads than ever, it is important to consider infrastructure options that safeguard cyclists and other road users whilst being cost effective and easily adaptable to cities that are constantly changing.
Keywords: 330